VARIATION IN THE COMPOSITION AND STRUCTURE OF NATURAL LOWLAND FORESTS AT BODOGOL, GUNUNG GEDE PANGRANGO NATIONAL PARK, WEST JAVA, INDONESIA - Asep Sadili; Andi Salamah; Edi Mirmanto; Kuswata Kartawinata (Reinwardtia, 2023)
An analysis of the composition and structure of lowland natural forests was carried out in Bodogol, Gunung Gede Pangrango National Park (GGPNP). The two study plots (P1CS and P2CS) were located on Cisuren and one plot (P3CP) on Cipadaranten hill. We recorded 107 species and 48 families with an average basal area of 19.73 m2/ha, and an average density of 348 trees/ha. The species richness was poorer than those of the typical lowland rainforests of Kalimantan and Sumatra but comparable to those of the montane forests of Java. The IUCN-Red Listed species were Castanopsis argentea and Castanopsis tungurrut (critical) and Saurauia bracteosa (vulnerable). Based on the two dominant species, the forests can be designated as the Maesopsis eminii-Syzygium acuminatissimum association and Syzygium acuminatissimum-Lithocarpus korthalsii association. Maesopsis eminii was dominant in P1CS (IV= 56.46%) and P3CP (IV=55.94%), while Syzygium acuminatissimum in P2CS (IV= 43.67%). Maesopsis eminii was a strongly aggressive and invasive species, that endangered the purity of the natural forest GGPNP, therefore, it must be eradicated. Vertically, P2CS and P3CP consisted of four strata, while P1CS had three strata. This one-hectare study can be considered as a minimal area to reflect the floristic representation of lowland forest and submontane forest.